Development of rice bran treatment process and its use for the synthesis of polyhydroxyalkanoates from rice bran hydrolysate solution. (April 2015) - Oh, Young Hoon; Lee, Seung Hwan; Jang, Young-Ah; Choi, Jae Woo; Hong, Kyung Sik; Yu, Ju Hyun; Shin, Jihoon; Song, Bong Keun; Mastan, Shaik G.; David, Yokimiko; Baylon, Mary Grace; Lee, Sang Yup; et al.
Highlights: Pretreatment process of rice bran was developed. Rice bran hydrolysate solution could support efficient growth of recombinant E. coli . Recombinant E. coli efficiently produced PHAs from rice bran hydrolysate solution. R. eutropha strains could efficiently grow from rice bran hydrolysate solution. R. eutropha strains efficiently produced PHAs from rice bran hydrolysate solution. Abstract: Rice bran treatment process for the production of 43.7 kg of hydrolysate solution containing 24.41 g/L of glucose and small amount of fructose from 5 kg of rice bran was developed and employed to produce polyhydroxyalkanoates in recombinant Escherichia coli and Ralstonia eutropha strains. Recombinant E. coli XL1-Blue expressing R. eutropha phaCAB genes and R. eutropha NCIMB11599 could produce poly(3-hydroxybutyrate) with the polymer contents of 90.1 wt% and 97.2 wt%, respectively, when they were cultured in chemically defined MR medium and chemically defined nitrogen free MR medium containing 10 mL/L of rice bran hydrolysate solution, respectively. Also, recombinant E. coli XL1-Blue and recombinant R. eutropha 437-540, both of which express the Pseudomonas sp. phaC1437 gene and the Clostridium propionicum pct540 gene could produce poly(3-hydroxybutyrate-co-lactate) from rice bran hydrolysate solution. These results suggest that rice bran may be a good renewable resource for the production of biomass-based polymers by recombinant microorganisms.